Examining the Development of China’s Low-Carbon Pilots: A Perspective of Non-Technological Innovation - SUN, Huilin; JIANG, Wei (Chinese journal of urban and environmental studies (Print), 2021)
This paper explores the non-technological innovation system for building low-carbon cities in China. It establishes a comprehensive evaluation index system and grading standards for low-carbon cities, concerning both technological innovation and non-technological innovation factors. Defining non-technological innovation factors as independent variables, GDP per capita as the main control variable, and low-carbon development and carbon productivity as dependent variables, this paper examines the contribution of non-technological innovation to the building of low-carbon cities. The result shows that non-technological innovation manifested a significant trajectory of progress. It demonstrates that the continuous improvement to non-technological innovation system should effectively promote the further development of low-carbon cities.